Demonstrators march on Sacramento in support of AB-1 - Sahl, Ted (photographer):::Creator::::::::::::
Five demonstrators march in a line down the middle of a street during the 1980 march on Sacramento in support of AB-1, proposed legislation banning employment discrimination based on sexual orientation. The two men on the right are Art Agnos and John L. Burton. A larger crowd carrying banners, signs and flags bearing AB-1 support slogans follow closely behind.